Antibacterial N-halamine fibrous materials. (December 2020) - Wang, Fei; Huang, Liqian; Zhang, Peng; Si, Yang; Yu, Jianyong; Ding, Bin
Abstract: Pathogenic microbial contamination poses serious threats to human healthcare and economies worldwide, which instigates the booming development of challenging antibacterial materials. N -halamine fibrous materials (NFMs), as an important part of antibacterial materials, featuring structural continuity, good pore connectivity, rapid sterilization, rechargeable bactericidal activity, and safety to humans and environment, have received significant research attention. This review aims to present a systematic discussion of the recent advances in N -halamine antibacterial fibrous materials. We firstly introduce the chemical structures and properties of N -halamine materials. Subsequently, the developed NFMs can be categorized based on their fabrication strategies, including surface modification and one-step spinning. Then some representative applications of these fibrous materials are highlighted. Finally, challenges and future research directions of the materials are discussed in the hope of giving suggestions for the following studies. Highlights: The chemical structures and properties of N -halamine materials are briefly introduced. Design and fabrication strategies of N -halamine fibrous materials are systematically reviewed. The functional applications of the N -halamine fibrous materials are discussed. Challenges and future research directions of the antibacterial N -halamine fibrous materials are provided.